Water justice struggles as a process of commoning. (7th December 2018) - Clark, Cristy
Abstract: This paper considers whether the act of articulating and claiming the human right to water can be described as a process of commoning . By considering short-case studies of water justice campaigns from Johannesburg, Michigan and Dublin, this paper will argue that the act of claiming the right to water is often an act of resistance to capitalism's process of accumulation by dispossession. It will also highlight the mobilizing and transformative effect of right to water activism, particularly amongst working-class communities, and the way that this activism has acted as a gateway to further counter-hegemonic political engagement. In this context, this paper argues that the right to water is not a claim to an individualistic right, but rather to a right of community resistance. This way of conceptualizing campaigns for the right to water challenges the idea that it is necessary to choose between a rights-based approach to water justice and one that focuses instead on reclaiming the commons.